2017
DOI: 10.1111/ipd.12298
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical study of plaque removal efficacy of a power toothbrush in a paediatric population

Abstract: Background. Clinical investigations of plaque removal efficacy of power toothbrushes in children are limited. Aim. To compare plaque removal of a power versus manual toothbrush in a paediatric population. Design. This was a randomised, replicate-use, single-brushing, examiner-blinded, two-treatment, four-period crossover clinical trial in children 8-11 years of age. Subjects were randomly assigned to a treatment sequence involving an oscillating-rotating power toothbrush and a manual toothbrush control. Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 16 publications
2
22
0
1
Order By: Relevance
“…evaluated the relative plaque‐reducing single‐use benefits of electric versus manual toothbrushes and stated, ‘A single brushing model provides a useful indication of the plaque removal ability of a toothbrush and facilitates control of confounding variables such as compliance, frequency of toothbrushing and probably even the Hawthorne and novelty effects.’ In that review, a sub‐analysis of the clinical trials using O‐R electric toothbrushes with pre‐ and post‐brushing scores found significantly superior TMQHPI plaque reduction ( P < 0.001) compared to a manual brush. Similarly in their crossover, single‐use clinical trial in a paediatric population, Davidovich et al 25 . reported a significant ( P < 0.001) between‐treatment TMQHPI difference of 0.233–0.298 (depending on examiner) in a paediatric population favouring the O‐R electric brush over the manual toothbrush; by comparison the benefit for the O‐R benefit was even larger in the current trial.…”
Section: Discussionsupporting
confidence: 61%
“…evaluated the relative plaque‐reducing single‐use benefits of electric versus manual toothbrushes and stated, ‘A single brushing model provides a useful indication of the plaque removal ability of a toothbrush and facilitates control of confounding variables such as compliance, frequency of toothbrushing and probably even the Hawthorne and novelty effects.’ In that review, a sub‐analysis of the clinical trials using O‐R electric toothbrushes with pre‐ and post‐brushing scores found significantly superior TMQHPI plaque reduction ( P < 0.001) compared to a manual brush. Similarly in their crossover, single‐use clinical trial in a paediatric population, Davidovich et al 25 . reported a significant ( P < 0.001) between‐treatment TMQHPI difference of 0.233–0.298 (depending on examiner) in a paediatric population favouring the O‐R electric brush over the manual toothbrush; by comparison the benefit for the O‐R benefit was even larger in the current trial.…”
Section: Discussionsupporting
confidence: 61%
“…Another study in children aged 6 to 11 years demonstrated superior plaque reduction with a Braun Oral‐B children's electric toothbrush relative to a manual brush over a 30‐day home use period and in single‐use supervised brushing at baseline 18 . Previous work from our group in 8 to 11 year olds showed superior plaque removal efficacy with a Braun Oral‐B children's electric toothbrush compared to a manual brush in a randomised, replicate‐use, single‐brushing, crossover clinical trial 15 …”
Section: Discussionmentioning
confidence: 85%
“…If the younger children had any permanent teeth, they were excluded from the analysis. A sample size calculation based on previous research using a similar study design 15 indicated 20 subjects completing in a 2‐treatment 4‐period crossover study would give a two‐tailed alpha = 0.1 with at least 80% power to detect a difference between treatments of at least 0.144 for mixed dentition and at least 0.141 for primary dentition. TMQHPI across the whole mouth (excluding any permanent teeth for the 3‐6 year old group) was the primary variable.…”
Section: Methodsmentioning
confidence: 99%
“…Cochrane Collaboration) to offer superior plaque removal and gingivitis reductions relative to various manual and electric toothbrush models 1‐3,11‐27 . Gingival health benefits have been demonstrated across various patient populations, including post‐surgical patients, pediatric patients, orthodontic patients, and adolescents 28‐32 . The O‐R movements disrupt and remove plaque via rapid shearing forces while the round brush head maximizes access in hard‐to‐reach areas.…”
Section: Introductionmentioning
confidence: 99%